2011
DOI: 10.3174/ajnr.a2588
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle Marrow Signal Hyperintensity on Short Tau Inversion Recovery- and T2-Weighted Images: Prevalence and Relationship to Clinical Symptoms

Abstract: BACKGROUND AND PURPOSE:Lumbar pedicle marrow hyperintense signal on T2-and STIR-weighted images is not an uncommon finding. We hypothesize that these marrow signal intensity changes and their behavior within the pedicle are associated with clinical symptoms and that their improvement or resolution correlates with clinical improvement. We investigated the prevalence of these pedicle marrow changes, associated morphologic abnormalities, and the relationship to symptoms over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
2
14
1
Order By: Relevance
“…Indeed, we found 7 SCs that were localized on the facet joint and did not affect the adjacent pedicle. The age of the study subjects also may have played a role in the different findings; mean age in our study was 62.8 years, compared with approximately 50 years in the previous studies 4,5) . There were two main findings related to the localization of the SCs: that 75% (27/36 SCs) were found at neighboring spinal levels across the facet joint, and that 36% (13/36 SCs) had continuity with Modic type 1 changes of the vertebral endplate.…”
Section: Discussioncontrasting
confidence: 37%
See 3 more Smart Citations
“…Indeed, we found 7 SCs that were localized on the facet joint and did not affect the adjacent pedicle. The age of the study subjects also may have played a role in the different findings; mean age in our study was 62.8 years, compared with approximately 50 years in the previous studies 4,5) . There were two main findings related to the localization of the SCs: that 75% (27/36 SCs) were found at neighboring spinal levels across the facet joint, and that 36% (13/36 SCs) had continuity with Modic type 1 changes of the vertebral endplate.…”
Section: Discussioncontrasting
confidence: 37%
“…In a previous study, the prevalence of SCs in MRIs of patients with low back pain was reported to be 1.8% (7/400), and 2 out of the 7 patients with SCs were <30 years of age, with no additional abnormal findings 5) . These differences in prevalence and age distribution could have resulted mainly from variations in the analysis method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This case highlights the importance of STIR MRI and diagnostic facet injection. The diagnostic utility of STIR MRI is optimal for ankylosing spondylitis (13), pedicle fracture and degenerative facet joints (14), and spondylolysis (15,16). Fluid collection, which is an indicator of inflammatory events, and bone marrow lesions, which could be micro bleeding in the bone marrow, can be evaluated on STIR MRI (17).…”
Section: Discussionmentioning
confidence: 99%